Bodies Matter: Professional Bodies and Embodiment in Institutional Sport Contexts. (August 2017) - van Amsterdam, Noortje; Claringbould, Inge; Knoppers, Annelies
Bodies are always present in organizations, yet they frequently remain unacknowledged or invisible including in sport organizations and sport management research. We therefore argue for an embodied turn in sport management research. The purpose of this article is to present possible reasons why scholars have rarely paid attention to bodies in sport organizations; to offer arguments why they should do so; and to give suggestions for what scholarship on bodies and embodiment might look like using various theoretical frameworks. Using the topic of diversity as an example, we explore what insights into embodiment and bodily practices the theoretical frameworks of Foucault, Bourdieu, Merleau-Ponty and Butler have to offer researchers and how these insights may lead to better understandings of organizational processes in sport.